Wastewater Treatment Using Microalgae / Azna binti Abdul Aziz - Abdul Aziz, Azna (2013)
Three species of selected microalgae isolated from Tasik Taman Jaya, Oscillatoria limnosa, Scenedesmus quadricauda and Pediastrum duplex, were cultured in Chu no. 10 defined medium. After the microalgae reached their optimum growth they were grown in wastewater to observe their capability to remove inorganic nutrients in wastewater. The microalgae showed steady increase in cell density for the duration of laboratory observation of eighteen days. As the cell density of the microalgae increased, both nitrate and phosphate concentration in wastewater decreased. This study showed that all the three species of microalgae have the ability to reduce the nutrients. Among them, Pediastrum duplex was most efficient in reducing inorganic nutrients in wastewater. It reduced 60% and 75% of the total nutrients of wastewater from Station A and Station B respectively. By using this biological wastewater treatment, less chemical and physical treatment is needed to improve wastewater quality. The biologically treated wastewater can then be discharged into the reservoirs, rivers or streams.